2014
DOI: 10.2147/cia.s66354
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bone tissue trace-element concentrations and mineral density in osteoporotic femoral neck fractures and osteoarthritis

Abstract: PurposeThis study examined the role of trace elements in osteoporosis by comparing the trace-element concentrations in bone and the radiographic bone density and bone mineral density (BMD) of patients with osteoporotic femur fractures and osteoarthritis.Patients and methodsThe study enrolled 30 patients operated on for proximal femoral fractures after falls, and another 30 patients undergoing hip arthroplasty at the same center for hip osteoarthritis. Bone samples were obtained during the surgical procedures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
1
15
3
Order By: Relevance
“…These were predominant elements in dog bone samples as well, although an even larger percentage was made up of light elements that could not be discriminated with our XRF analyzer. A decrease in Ca and P in compact bone reduces bone mineral density (BMD) and is characteristic of osteoporosis [20,21]. However, neither Ca nor P percentages were reduced in OA samples of either bone type in this study, even in the severe cases.…”
Section: Discussioncontrasting
confidence: 64%
“…These were predominant elements in dog bone samples as well, although an even larger percentage was made up of light elements that could not be discriminated with our XRF analyzer. A decrease in Ca and P in compact bone reduces bone mineral density (BMD) and is characteristic of osteoporosis [20,21]. However, neither Ca nor P percentages were reduced in OA samples of either bone type in this study, even in the severe cases.…”
Section: Discussioncontrasting
confidence: 64%
“…Diseases such as osteoarthritis (OA), coxarthrosis, osteoporosis, and bone cancers including osteogenic sarcoma may be accompanied by normal, reduced, or elevated Cr, V, and Ca concentrations [ 6 , 21 , 22 ]. Karaaslan et al [ 23 ] in Turkey found that V concentration in patients with OA did not exceed 22 µ g/g dm but was two orders of magnitude greater than in patients with OA in this study. Noor et al [ 24 ] showed that V concentration was higher but Cr and Ca were lower in OA patients than without OA subjects.…”
Section: Discussioncontrasting
confidence: 57%
“…In recent years, the decrease of trace elements caused by severe trauma has begun to be paid attention to, and have demonstrated that changes in trace elements are different in different degrees and damage from brain injury, fracture, and burn injury. [ 5 , 6 ]…”
Section: Introductionmentioning
confidence: 99%